Cultural and Religious Belief Approaches of a Tuberculosis Program for Hard-to-Reach Populations in Mentawai and Solok West Sumatera, Indonesia - Machmud, Rizanda; Medison, Irvan; Yani, Finny Fitry (Kesmas, 2020)
Tuberculosis (TB) is a leading public health concern in Indonesia. It ranks second on the list of high-burden TB countries. In West Sumatra, 47% of TB cases are undetected, late diagnosed, and received incomplete treatment because of low-level awareness and knowledge and stigma, especially among the hardest to reach populations. The study aims to identify the best communication channel to reach those who live in vulnerable and remote areas. This study was a qualitative study applying in-depth interviews to the informal leaders, health officers, cultural artists, and religious leaders across districts in Mentawai and Solok Districts, which are remote and had the lowest case detection rates compared with other districts. The questionnaire was prepared with the perception of the channel to identify TB cases. The data were analyzed using the content analysis technique. Involving religious and informal leaders and using traditional music as a communication channel improved the population's awareness of TB symptoms and access to TB testing and treatment, as well as reduced TB-related stigma. This study found that the cultural and religious contexts play a major role in health communication on TB control for hard-to-reach populations in West Sumatera, Indonesia.